Difference Between Posterior Monteggia Fractures and Posterior Fracture‐Dislocation of Proximal Ulna in Adults. Issue 5 (13th August 2020) - Liu, Jun‐yang; Zhang, Ji‐zheng; Wang, Ye‐ming; Tian, Xu; Dong, Jing‐ming
Abstract : Objective: To figure out the difference between patients with posterior Monteggia fractures which were concomitant with proximal radioulnar joint (PRUJ) dislocation and posterior fracture‐dislocation of the proximal ulna that were not concomitant with PRUJ. Methods: From January 2016 to January 2019, 37 consecutive adult patients who had posterior fracture‐dislocation of proximal ulna (no PRUJ dislocation, n = 16) and posterior Monteggia fractures (PRUJ dislocation, n = 21) were included. All patients had intraoperative fluoroscopy, computed tomography (CT) scans, and standard radiography (anteroposterior view and lateral view). The mechanism of injury, the cases with open fracture, sustained multiple injuries and classification of fracture was recorded. The clinical details of the patients such as the final range of motion (ROM) and the Broberg–Morrey scores were described. Results: Patients with PRUJ dislocation (ten type A, five type B, and six type D) and those without concomitant PRUJ dislocation (fifteen type A and one type C) exhibited an obvious difference according to the classifications of Jupiter et al. ( P = 0.010). Ninety‐five percent of patients who had PRUJ dislocation were accompanied by a metaphyseal fracture, while only 50% of the patients who did not have PRUJ dislocation were accompanied by a metaphyseal fracture ( P = 0.002). Meanwhile, 16 of 20 metaphyseal fractures had more than one fragment in the group of dislocations, but five of eight metaphyseal fractures were comminuted in the control group. The two groups exhibited an obvious difference ( P = 0.009). The 21 patients who sustained a radioulnar dislocation had less mean arc of flexion, pronation, and Broberg–Morrey scores were significantly less than the patients of the control group (flexion: 117.38 ± 14.46 vs 127.50 ± 13.416, P = 0.035; pronation: 59.76 ± 11.88 vs 67.50 ± 6.58, P = 0.017; Broberg–Morrey: 80.48 ± 12.17 vs 88.19 ± 10.28, P = 0.040). Conclusions: Patients suffering posterior Monteggia fractures had more metaphyseal fractures, more comminuted fractures of the metaphysis, and worse ultimate ulnohumeral motion than patients of posterior fracture‐dislocation of proximal ulna. Abstract : A‐B, posterior Monteggia fractures had comminuted fracture of metaphysis and dislocation of PRUJ. C‐D, posterior fracture‐dislocation of proximal ulna didn't have fracture of metaphysis and no dislocation of PRUJ.